2017
DOI: 10.1007/s00431-017-3030-9
|View full text |Cite
|
Sign up to set email alerts
|

Late-onset sepsis due to urinary tract infection in very preterm neonates is not uncommon

Abstract: Urinary tract infection (UTI) is a common cause of sepsis in infants. Premature infants hospitalized at a neonatal intensive care unit often have risk factors for infection. In this group, the risk of UTI is not clearly known, and guidelines for urine analysis are not unanimous. We aimed to identify the risk of UTI in premature infants with central lines, suspected of late-onset sepsis. We analyzed all 1402 infants admitted to our hospital between 2006 and 2014 with a gestational age less than 32 weeks. Six hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 19 publications
(24 reference statements)
0
22
0
1
Order By: Relevance
“…Additionally, our study revealed that the rate of UTI was non-significantly higher among fullterm neonates. In contrast, Mohseny et al [3] reported a high risk (11.3%) of UTI in NICU-admitted premature infants (less than 32 weeks) with central line and suspected sepsis. They attributed this high frequency to the presence of many risk factors for infection in preterm neonates.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Additionally, our study revealed that the rate of UTI was non-significantly higher among fullterm neonates. In contrast, Mohseny et al [3] reported a high risk (11.3%) of UTI in NICU-admitted premature infants (less than 32 weeks) with central line and suspected sepsis. They attributed this high frequency to the presence of many risk factors for infection in preterm neonates.…”
Section: Discussionmentioning
confidence: 88%
“…However, the true prevalence of UTI in preterm neonates is difficult to determine, as sterile urine cultures are not reliably obtained in all suspected sepsis assessments. The assumed complications of sterile catheterization or suprapubic aspiration hinder urine collection, and alternative collection methods such as bag collection have high rates of contamination [3].…”
Section: Introductionmentioning
confidence: 99%
“…Risk factors for bacteremia include prematurity, young age (< 1 year), and high serum creatinine at presentation [109]. Late-onset sepsis due to UTI is not uncommon in infants with a gestational age of less than 32 weeks [110]. Febrile convulsion may occur in young children with high fever from pyelonephritis [111, 112].…”
Section: Complicationsmentioning
confidence: 99%
“…Bacteramia is not uncommon in UTI, both in community and hospital settings and in all age groupsadults, elderly and neonates; but the burden varied widely in different studies. [11][12][13] Generally, outcome of UTI complicated by bacteramia is worse than those without. 14 In the present study, we found nearly 7% of our type 2 diabetic subjects diagnosed with UTI had concomitant bacteramia.…”
Section: Discussionmentioning
confidence: 99%